2016
DOI: 10.1080/0092623x.2016.1164783
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Premature Ovarian Failure Awareness in Female Sexual Functions and Distress

Abstract: The diagnosis of premature ovarian failure is traumatic to women, with loss of gonadal functions having been associated with distress and anxiety. The aim of this study is to evaluate the sexual function and distress of women with premature ovarian failure before the diagnosis. Women with premature ovarian failure and age-matched controls were evaluated through the Female Sexual Function Index and the Female Sexual Distress Scale-Revised, and their androgen levels were compared. The major finding of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The actual difference in TTO values between the groups is small and may not reflect an overall clinical significant difference but these analyses are group based and the individual differences should not be ignored when working with these patient groups. Our result is in line with previous studies on the same subject [ 13 , 22 , 23 ]. However, contradictory results have also been published, where long-time cancer survivors in the USA scored higher on well-being measures as self-reported health, utility and happiness [ 36 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The actual difference in TTO values between the groups is small and may not reflect an overall clinical significant difference but these analyses are group based and the individual differences should not be ignored when working with these patient groups. Our result is in line with previous studies on the same subject [ 13 , 22 , 23 ]. However, contradictory results have also been published, where long-time cancer survivors in the USA scored higher on well-being measures as self-reported health, utility and happiness [ 36 ].…”
Section: Discussionsupporting
confidence: 94%
“…Although cancer survivors had a strong desire for having children [15,18], they were worrying about the health of a future biological child [19,20] as well as their own health [21]. Additionally, several studies have confirmed a link between POI and quality of life (QoL) and depression [22,23]. The objective of this study was therefore to investigate QoL and health state (as defined by the EQ-5D-3L questionnaire) [24][25][26] among female CCS with and without POI and healthy controls (HC).…”
Section: Introductionmentioning
confidence: 99%
“…Third, understanding the variations in sexual function across different conditions can inform more personalized approaches to treatment and support for affected women. Previous research has predominantly focused on the reproductive implications of PCOS and POI, with less emphasis on other critical areas like sexual satisfaction and function [9,10]. Studies that do address sexual function often fail to compare different types of ovarian dysfunction, thereby missing out on potential nuances in their impacts on sexual health.…”
Section: Introductionmentioning
confidence: 99%